Indonesian in Andrea Hirata’s Edensor - Sukarni Suryaningsih (Faculty of Humanities, Diponegoro University, 2022)
Culture is one of the uniqueness of humans that makes it have a way of surviving in the world. If animals grow anatomical organs to adapt and survive, then humans grow culture. Culture is our adaptive organ, it is our survival mechanism. This cultural world is an order of existence like no other because it is not shared by any other species. Culture adapts more quickly to new situations than changes in anatomy. That is why humans can move from one environment to another, whereas animals cannot. Culture is a collective product that includes general behavior, perception, emotion, self, and motivation, which then synthesizes individual behavior in a new form. The behavior of all individuals involved in a particular context is not always uniform or identical, but sociocultural contexts can shape people in various ways. Indonesian society has a cultural mentality that refers to a number of distinctive characteristics, both individuals and community groups which then can be a distinguishing feature from other nations. A friendly, helpful, and mutually cooperative character is some of the most often attributed to the nature of the Indonesian people. Literature as a cultural product can be a means to see the mental identity of the culture. The Edensor, a novel by Andrea Hirata, shows how the representation of Indonesian students and their mental and cultural identity in the midst of international relations, with Sorbonne University students. Through qualitative descriptive research with a constructionist approach from Stuart Hall's representation theory, this study's results indicate that Indonesian students' representation is tenacious, easily fascinated especially by Western society and culture, and tend to believe in superstition.